Metabolic potential of microbial community and distribution mechanism of Staphylococcus species during broad bean paste fermentation. (October 2021) - Jia, Yun; Niu, Cheng-Tuo; Xu, Xin; Zheng, Fei-Yun; Liu, Chun-Feng; Wang, Jin-Jing; Lu, Zhen-Ming; Xu, Zheng-Hong; Li, Qi
Graphical abstract: Highlights: Five genera were predominant populations responsible for substrate alteration and flavor formation. Staphylococcus was the most abundant functional genus in broad bean paste. Staphylococcus gallinarum was the most abundant Staphylococcus specie. BBP environment led to dominant position and species coexistence of Staphylococcus . Congeneric competition shaped ecological distributions of Staphylococcus species. Abstract: Although the microbial diversity and structure in bean-based fermented foods have been widely studied, systematic studies on functional microbiota and mechanism of community forms in multi-microbial fermentation systems were still lacking. In this work, the metabolic pathway and functional potential of microbial community in broad bean paste (BBP) were investigated by metagenomics approach, and Staphylococcus, Bacillus, Weissella, Aspergillus and Zygosaccharomyces were found to be the potential predominant populations responsible for substrate alteration and flavor biosynthesis. Among them, Staphylococcus was the most abundant and widespread functional microbe, and closely related Staphylococcus species were diverse and ubiquitously distributed, with the opportunistic pathogen S . gallinarum being the most abundant Staphylococcus specie isolated from BBP. To explain the dominance status of S. gallinarum and species distributions of Staphylococcus genus, we tested the effects of abiotic and biotic factors on three Staphylococcus species using a tractable BBP model, demonstrating that adaptation to environmental conditions (environmental parameters and other functional microbes) led to the dominant position and species coexistence of Staphylococcus, and congeneric competition among Staphylococcus species further shaped ecological distributions of closely related Staphylococcus species. In general, this work revealed the metabolic potential of microbial community and distribution mechanism of Staphylococcus species during BBP fermentation, which could help traditional factories to more precisely control the safety and quality of bean-based fermented foods.